2014
DOI: 10.1186/1756-3305-7-136
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric evaluation of the recombinant Leishmania infantum antigen-based immunochromatographic assay for the serodiagnosis of canine visceral leishmaniasis

Abstract: BackgroundVisceral leishmaniasis (VL) is a serious public health challenge in Brazil and dogs are considered to be the main urban reservoir of the causative agent. The culling of animals to control VL in some countries makes the accurate diagnosis of canine VL (CVL) essential. Recombinant antigens rLci1A and rLci2B were selected from a cDNA library of Leishmania infantum amastigotes due to their strong potential as candidates in diagnostic testing for CVL. The present multicentric study aimed to evaluate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Moreover, two of these proteins was already tested in a DPP platform, an immunochromatographic rapid test prototype based on the dual path platform. The sensitivity of the DPP Prototype with Lci1A and Lci2B evaluated in a multi-centric study was 87%, similarly to the 88% of sensitivity from the test currently provided by the Brazilian Minister of Health, DPP-LVC [ 16 ]. The present study aimed to evaluate the accuracy of the recombinant antigens (Lci1A, Lci2B, Lci4, Lci5, Lci8 and Lci12) of Leishmania infantum for the serodiagnosis of dogs infected by L .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, two of these proteins was already tested in a DPP platform, an immunochromatographic rapid test prototype based on the dual path platform. The sensitivity of the DPP Prototype with Lci1A and Lci2B evaluated in a multi-centric study was 87%, similarly to the 88% of sensitivity from the test currently provided by the Brazilian Minister of Health, DPP-LVC [ 16 ]. The present study aimed to evaluate the accuracy of the recombinant antigens (Lci1A, Lci2B, Lci4, Lci5, Lci8 and Lci12) of Leishmania infantum for the serodiagnosis of dogs infected by L .…”
Section: Introductionmentioning
confidence: 76%
“…A set of six recombinant L . infantum antigens (rLci1A, rLci2B, rLci4, rLci5, rLci8, rLci12) was previously selected from a cDNA and a genomic library of Leishmania infantum based on antibody reactivity using a pool of sera from culture-positive dogs and human patients with VL [ 11 , 16 ]. These recombinant antigens were screened using a multi-antigen print immunoassay (MAPIA) [ 14 ] technique to verify potential as viable candidates in diagnostic testing.…”
Section: Methodsmentioning
confidence: 99%
“…(24,25) In fact, the DPP ® CVL test was developed for joint detection of antibodies against K26 and K39 antigens, (26) and historically, studies of the anti-Leishmania canine chromatographic immunoassay formulation have indicated an increased sensitivity when using both antigens together, while the use of k39 or rk39 in isolation has resulted in lower sensitivities. (27,28) Subsequently, although Otranto et al (29) reached high sensitivity with the use of the rk39 antigen alone, other studies have suggested that the combined use of different antigens is associated with increased sensitivity in immunochromatographic tests; (17,25,30) Souza Filho et al (31) demonstrated high sensitivity with the use of the Alere TM test, which also utilises chimaera rK28. High sensitivity is a characteristic required when using diagnostic tests as a screening tool for the Visceral Leishmaniasis Control Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the antigens tested showed very good potential for the canine form, with one of them (Lci13), demonstrating a better capacity to detect the canine leishmaniasis than the total parasite lysate. This protein is a promising antigen, since some recent studies did not find a single protein capable of such diagnostic efficiency in dogs [ 38 , 39 ]. In contrast, none of the antigens tested were as effective for human VL, highlighting the differences in immune response between the two different disease targets, as highlighted previously [ 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%